Beyond the Average Elasticity – Applying Quantile Panel Regression to German Household Mobility Data - Nolan Ritter (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This paper employs quantile panel regression to the study of fuel price elasticities. Contrasting with standard panel approaches, this method reveals the impact of explanatory variables across all points in the conditional distribution of the response variable while controlling for unobserved heterogeneity. Applying quantile panel regression to German household data demonstrates that fuel price elasticities are very high in magnitude - below -0.8 - for a small segment of households whose car mileage is low, but that this effect tapers off rapidly among households with higher car mileage. These findings have implications for policy instruments that rely on estimates of fuel price elasticities, for example fuel taxation. – – Diese Studie untersucht Kraftstoffpreiselastizitäten unter Verwendung von Quantils-Panelschätzern. Im Gegensatz zu den üblicherweise verwendeten Panelansätzen kann mittels Quantils-Panelschätzern der Einfluss der erklärenden Variablen an beliebigen Punkten in der bedingten Verteilung der abhängigen Variablen geschätzt werden, während gleichzeitig für unbeobachtbare Heterogenität kontrolliert wird. Anhand des Deutschen Mobilitätspanels kann mittels dieser Methode gezeigt werden, dass die Kraftstoffpreiselastizität sehr hoch für Haushalte mit einer niedrigen Fahrleistung ausfällt, während Haushalte mit hoher Fahrleistung eine geringe Kraftstoffpreiselastizität aufweisen. Diese neue Erkenntnis besitzt Implikationen für die Besteuerung von Kraftstoffen.
Keywords: C21; C23; D13; Q41; 330; price elasticity; panel data; quantile regression